Application of a Radio Frequency Identification System for Supporting the Performance of Motorcycle Parking in Narotama University - Mudjanarko, Sri Wiwoho; Purworusmiardi, Tubagus (Universitas Muhammadiyah Malang, 2017)
The increasing number of motorcycles in Indonesia creates enormous problems because of the hectic involved; thus, parking management becomes a big challenge. The applicability and the possibility of a Radio Frequency Identification (RFID) were studied in finding the solution of this pressing issue. The study was conducted at Narotama University which is located in Surabaya, East Java. This study was expected to find solutions related to provide parking facilities using RFID method to identify motorcycles. The goal of this study is to determine the number of motorcycle vehicles which is being parked electronically to facilitate the management in organizing motorcycle in parking facilities. Hence, the management can arrange the requirement of parking system in the future. From the study, it can be concluded that RFID can make the process faster and easier so that the line can significantly be reduced and provide more user friendly system because the system will give the information about parking availability. Moreover, this RFID parking system and the software can be more reliable and secured due to more complete and accurate data in the registration process required to the users.